2004
DOI: 10.1111/j.1365-2389.2004.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural differences between bulk and rhizosphere soil

Abstract: The physical characteristics of the soil at the root–soil interface are crucial because they determine both physical aspects of root function such as water and nutrient uptake and the microbial activity that is most relevant to root growth. Because of this we have studied how root activity modifies the structure and water retention characteristic of soil adjacent to the root for maize, wheat and barley. These plants were grown in pots for a 6-week growth period, then the soil adjacent to the root (rhizosphere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
0
16

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 30 publications
8
123
0
16
Order By: Relevance
“…We refer to several recent reviews on the specific physical, chemical, biological properties of the rhizosphere (Gregory 2006;Hinsinger et al 2009); to measurements of water content (Young 1995), structure (Whalley et al 2005), wettability (Read et al 2003), and mechanical stability (Czarnes et al 2000) of the rhizosphere compared to bulk soil; to in-situ infiltration in the rhizosphere (Hallet et al 2003); and to recent observations of unexpected water dynamics in the rhizosphere (Carminati et al 2010). These studies show several controversies, for example in whether the rhizosphere has increased or decreased water content and conductivity compared to the bulk soil.…”
Section: Introductionmentioning
confidence: 99%
“…We refer to several recent reviews on the specific physical, chemical, biological properties of the rhizosphere (Gregory 2006;Hinsinger et al 2009); to measurements of water content (Young 1995), structure (Whalley et al 2005), wettability (Read et al 2003), and mechanical stability (Czarnes et al 2000) of the rhizosphere compared to bulk soil; to in-situ infiltration in the rhizosphere (Hallet et al 2003); and to recent observations of unexpected water dynamics in the rhizosphere (Carminati et al 2010). These studies show several controversies, for example in whether the rhizosphere has increased or decreased water content and conductivity compared to the bulk soil.…”
Section: Introductionmentioning
confidence: 99%
“…Several of the shape parameters have been previously used to determine aggregate characteristics in soils 22 . 125…”
Section: Analysis 90mentioning
confidence: 99%
“…While the volume occupied by roots in such soils may be small, the physical environment is quite different to that measured in the bulk soil. Whalley et al (2005) demonstrated that water retention and aeration properties of the rhizosphere soil are enhanced with respect to root growth compared to the properties of the bulk soil. Passioura (2002) describes the many interactions between root and soil that demonstrate the ability of plants to adapt to and survive in stressed situations.…”
Section: Glbd Llwr and The Rhizospherementioning
confidence: 99%